Percepción del entorno y reactividad cardiovascular - Fernández Abascal, E. G.; Vallejo, M. Á.; Labrador, F. J.; Roa, A.; Calvo, F.; Domínguez, F. (Análisis y Modificación de Conducta, 2013)
Sin resumen